2003
DOI: 10.1345/aph.1c361
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Linezolid-Induced Anemia and Thrombocytopenia

Abstract: There appear to be 2 distinct mechanisms for linezolid-induced cytopenias. While anemia is reversible and manageable with transfusions, thrombocytopenia can be a treatment-limiting toxicity. The ability to treat through an immune-mediated cytopenia with IVIG may be beneficial for critically ill patients with few therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
113
1
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 12 publications
7
113
1
4
Order By: Relevance
“…Furthermore, no drug-related changes in vital signs or in clinical chemistry, urinalysis, or hematology values were observed. This confirms the fact that linezolid is well tolerated (5), even in cancer patients (25), and only a few adverse effects were reported (3,29).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, no drug-related changes in vital signs or in clinical chemistry, urinalysis, or hematology values were observed. This confirms the fact that linezolid is well tolerated (5), even in cancer patients (25), and only a few adverse effects were reported (3,29).…”
Section: Discussionsupporting
confidence: 81%
“…In those studies, tedizolid was also without hematopoietic toxicity at exposures up to 4 to 7 times the human-equivalent exposure, whereas linezolid toxicity was evident at drug levels comparable to the corresponding humanequivalent exposure (25,56,57). Hematopoietic effects of linezolid are believed to be the result of MPS inhibition in bone marrow cells (2,25,56,58). In the clinical setting, results from two phase 3 trials conducted in patients (n Ï­ 1,333) with acute bacterial skin and skin structure infections indicated that tedizolid given at 200 mg once daily for 6 days resulted in a lower incidence of adverse changes in hematologic parameters, in particular platelets, than that with linezolid given at 600 mg twice daily for 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…5 Taking into account that peripheral blood cells were reduced in such short term (30 min) in our study, we consider as less likely that this is a result of bone marrow suppression. Yet, further research is needed to find the real mechanism.…”
Section: Discussionmentioning
confidence: 69%
“…[2][3][4] Reversible myelosuppression and immunemediated toxicity have been suggested as potential explanations for this observation. 3,5,6 In the current era, obesity seems to acquire an epidemic profile, especially in developed countries. Published evidence suggests that the outcome of infections may be associated with body mass index distribution.…”
Section: Introductionmentioning
confidence: 99%